2003
DOI: 10.5144/0256-4947.2003.264
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inhalation Technique in Primary Care Asthmatic Patients Using Metered-Dose Inhalers with or without a Spacer

Abstract: Background: Asthma is a chronic disease with increasing morbidity and mortality. Although the development of metered-dose inhalers (MDIs) was a landmark in asthma management, their use is burdened by inappropriate training. Inadequate inhalation technique is reported in 24% to 89% of patients. We assessed how a sample of adult asthmatic patients seen in primary healthcare clinics (PHCs) in Riyadh used their metered-dose inhalers (MDI). Patients and Methods:We conducted a cross-sectional survey of asthmatic adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…In a study of pharmacist dispensing of pMDIs, it was shown that specific instruction on pMDI technique during the training period and periodic continuing education during professional practice promotes better patient education. 15 We believe the same is true for pediatricians.…”
Section: -11mentioning
confidence: 57%
See 3 more Smart Citations
“…In a study of pharmacist dispensing of pMDIs, it was shown that specific instruction on pMDI technique during the training period and periodic continuing education during professional practice promotes better patient education. 15 We believe the same is true for pediatricians.…”
Section: -11mentioning
confidence: 57%
“…It is tempting to suggest but hard to prove that errors committed by patients are the result of the lack of skill in use of the devices among physicians. 14 Other investigators 15 found that patients with asthma whose physicians were more skillful with inhalers were significantly more competent themselves with inhalers than were patients whose physicians were less skillful. In a study of pharmacist dispensing of pMDIs, it was shown that specific instruction on pMDI technique during the training period and periodic continuing education during professional practice promotes better patient education.…”
Section: -11mentioning
confidence: 99%
See 2 more Smart Citations
“…Factors leading to nonadherence may be related to poor inhaler technique, a regimen with multiple drugs, concern regarding side effects from the drugs, or the cost of medications. [9899100] Other factors include: lack of knowledge about asthma, lack of partnership in the management, inappropriate expectations, underestimation of asthma control, use of unconventional therapy and cultural issues. [101102]…”
Section: Approach To Asthma Managementmentioning
confidence: 99%